HERBAL CREAMS OF REISHI EXTRACT AND TEA TREE OIL FOR HIRSUTISM–AN IN VIVO STUDY - CHOUDHURY, SANGEETA; MADHAVI, BLR (International Journal of Current Pharmaceutical Research, 2020)
Objective: The aim of this work to formulate, evaluate and compare the effectiveness of herbal creams containing extract of reishi and tea tree oil for treating hirsutism. Methods: Herbal ingredients were authenticated. Cream base was initially formulated. Three formulations of herbal cream were prepared. Reishi ethanolic extract, tea tree oil, and combination of tea tree oil and reishi extract were added to the cream base and formulated cream were named as RHC, THC and RTC respectively. In vitro evaluations on herbal creams were done for the physicochemical characteristics. In vivo studies were carried out on female Swiss Albino mice for the activity against hair growth by topical application of cream to shaved skin. The histological and morphometric evaluation was carried out. Skin irritancy study was conducted. Results: The herbal creams showed desirable physicochemical properties like pH, viscosity and spreadability. Statistical analysis for the length of hair was performed by using one way ANOVA followed by DUNNET’S post hoc test where THC and RTC were found to be significant whereas RHC showed no significant reduction of hair growth compared to control. RTC showed a significant effect at p<0.05 and hair growth reduction was significant for THC at p<0.001 compared to the control group. RTC and THC showed mild to moderate reduction in the size of the hair follicles with a reduction of sebaceous gland size in the histological analysis. Conclusion: Topical application of herbal creams to mice showed that hair growth was fastest in group RHC and was slowest in group THC and intermediate with RTC. It can be concluded that these herbal actives can be used as an effective treatment against hirsutism. Within the study period, tea tree oil was found to be more effective than reishi extract and the combination product. Further formulation studies and in vivo studies need to be carried out on reishi to assess its effectiveness against hirsutism.